Pengaruh Pemberian Seduhan Daun Kelor Terhadap Gula Darah Penderita Diabetes Melitus Tipe II - sonny rosina; Yesi iHasneIi; Gamya Tri Utami (HEALTH CARE: JURNAL KESEHATAN, 2022)
Abstract Non-pharmacological therapy is needed by sufferers of type 2 diabetes and it is believed that Moringa leaves contain flavonoids which are substances to lower blood sugar levels. This study aims to determine the effect of infusion of Moringa leaves on the blood sugar of type II diabetes mellitus sufferers. This study is a quasi-experimental research design with a pre-posttest group design. The research sample was 34 people who were taken based on inclusion criteria using purposive sampling technique. Analysis using the Mann Whitney test. The results of the Wilcoxon test in the experimental group before and after consuming the steeping of moringa leaves obtained p value 0.003 <Î± (0.05). The results of the T dependent test for the control group before and after the test showed a p value of 0.436> Î± (0.05). The results of the Mann Whitney test in the experimental group and the control group showed the difference between pretest and posttest blood sugar levels with a p value of 0.004 <Î± (0.05). So it can be concluded that Ho is rejected, which means that consumption of steeping Moringa leaves is effective in reducing blood sugar levels in type II DM patients. Moringa leaves contain flavonoids which are antioxidants so that they can inhibit the damage that occurs to pancreatic beta cells so that they can reduce blood sugar levels. The consumption of moringa leaf infusion is effective in reducing blood sugar levels in type II DM patients